Analysing entrepreneurs' personality - Németh Gergely; Kis-Tamás Loránd (2016)
Concerning the purpose of my thesis I decided that instead of questions and answers I would provide rather a short article wherein I raise the questions. An incalculably great theme lies behind the questions - What kind of personality makes an entrepreneur successful? Who is an entrepreneur? What kinds of roles can he fulfill? What can be concluded from his behaviour? How does he make decisions and what patterns of behaviour can be concluded from this? What is entrepreneurial success? I was a little uncomfortable since, as an organizational psychologist, I do not believe that we can define a detailed personality profile in order to perform a particular occupation or profession. We can only dissertate among other things what kind of personality elements make a certain profession successful. Rather, I believe that there are behavioural elements that can assist good cooperation between partners.